1969
DOI: 10.1071/bi9690905
|View full text |Cite
|
Sign up to set email alerts
|

Identity of the Fungal Symbiont of Sirex Noctilio

Abstract: SummaryThe fungus associated with S. noctilio F. in Australia is identified as Amylostereum areolatum (Fr.) Boidin. By using a polystyrene film to prevent the breakup of the chains of arthrospores during staining, it was possible to demonstrate that the spores are homokaryotic though usually multinucleate. Viable homokaryons were established from arthrospores by using a tissue culture medium incorporating growing callus tissue of Pinus radiata. Homokaryons and heterokaryons of the S. noctilio fungus were oppos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

1973
1973
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 14 publications
1
20
0
Order By: Relevance
“…Single drills generally contain only colourless phytotoxic mucus and arthrospores of the pathogenic basidiomycete Amylostereum areolatum (Fries) Boidin ( Figure 6) (Gaut 1969, Coutts 1969a, which is an obligate symbiont of S. noctilio (Buchner 1928;Cartwright 1929Cartwright , 1938Clark 1933). Single drills are believed to be made mainly for testing the suitability of the substrate for oviposition, or for predisposing the host to subsequent attack.…”
Section: Life History and Symbiosismentioning
confidence: 99%
See 1 more Smart Citation
“…Single drills generally contain only colourless phytotoxic mucus and arthrospores of the pathogenic basidiomycete Amylostereum areolatum (Fries) Boidin ( Figure 6) (Gaut 1969, Coutts 1969a, which is an obligate symbiont of S. noctilio (Buchner 1928;Cartwright 1929Cartwright , 1938Clark 1933). Single drills are believed to be made mainly for testing the suitability of the substrate for oviposition, or for predisposing the host to subsequent attack.…”
Section: Life History and Symbiosismentioning
confidence: 99%
“…Arthrospores of A. areolatum within a parental hypha, from a culture on V8 agar. The arthrospores are multi-nucleate and homokaryotic (Gaut 1969): a. arthrospore' b. cross wall; c. parental hyphal wall.…”
Section: Life History and Symbiosismentioning
confidence: 99%
“…: Fr. ) Boidin, A. chailletfi, and A. laevigatum are known as symbionts of both Sirex and Urocerus (Gaut, 1969(Gaut, , 1970Sano et al, 1995;Tabata and Abe, 1997). Gaut (1970) found that the same horntail species always associated with the same fungal species.…”
Section: Resultsmentioning
confidence: 95%
“…japonica. Amylostereum laevigatum is different from A. chailletii, which is known as a symbiont of Sirex and Urocerus species (Gaut, 1969(Gaut, , 1970. Eriksson and Ryvarden (1973), Breitenbach and Kr~nzlin (1986), and Chamuris (1988) state that the basidiocarps of A.…”
Section: Resultsmentioning
confidence: 99%